Root growth and production of organic acids by soybean cultivars with different tolerance to aluminum - Menosso, Orival Gastão; Costa, José Antonio; Anghinoni, Ibanor; Bohnen, Humberto (Pesquisa Agropecuaria Brasileira, 2001)
The understanding of the mechanisms for the differential performance of soybean genotypes in relation to Al toxicity is important to explore the existing or produced genetic variability. The objective of this study was to determine the Al influence on root growth, solution pH modifications and organic acid content in root extracts of Al tolerant, FT-1 and FT-6 (Veneza) and sensitive, IAC-13 and Paraná, soybean cultivars. Plants were grown during nine days in a solution containing 50 mg L-1 of calcium and 0.0 and 0.2 mg L-1 of aluminum. The solution pH at the beginning was 4.76. Root growth in Al solutions of the tolerant soybean cultivars was higher than that of the sensitive ones. There was no solution pH modification related to the tolerance of soybean cultivars to aluminum. The content of citric, lactic, succinic, oxalic and malic acids was reduced in all cultivars in the presence of aluminum. The highest reduction was observed in the Al sensitive cultivars. The largest amount of citric acid was found in the tolerant cultivars. Tolerance of soybean cultivars can be expressed by the content of non-volatile organic acids, particularly of the citric acid. These characteristics, expressed by the FT-1 and FT-6 (Veneza), suggest that it can be a very important mechanism for Al tolerance in soybean.